A metal-free and air-tolerable insertion polymerization using sulfoxonium ylides as monomers. (5th October 2022) - Wang, Xiao-Qing; Bai, Yu-Qing; Wang, Kun; Wu, Bo; Zhou, Yong-Gui
Graphical abstract: Highlights: Metal-free and air-tolerable insertion polymerization using sulfoxonium ylides as monomers. Polythioethers with good thermal properties. Insertion polymerization features mild condition, easy operation and broad substrate scope. Abstract: Insertion polymerization represents a concise approach to construct carbon-heteroatom bonds in the main chain. Despite some momentous efforts have been devoted to transition-metal catalyzed insertion polymerization, the metal-free insertion polymerization remains elusive. Herein, the fascinating metal-free and air-tolerable insertion polymerization using sulfoxonium ylides as monomers has been disclosed, furnishing a plethora of polythioethers and aromatic polyamines with carbon-heteroatom bonds in the main chain (yield up to 99%, Mn up to 20100). The insertion polymerization features mild condition, easy operation and broad substrate scope. In addition, thermal analysis demonstrated the polymers exhibited good thermal properties.